Adaptive scheduling of acceleration and gyroscope for motion artifact cancelation in photoplethysmography. (November 2022) - Lee, Hooseok; Chung, Heewon; Ko, Hoon; Parisi, Antonino; Busacca, Alessandro; Faes, Luca; Pernice, Riccardo; Lee, Jinseok
Highlights: We present how the acceleration and gyroscope signals correlate with the motion artifacts (MAs) of PPG signals. We demonstrate HR estimation using PPG signals can be inaccurate even with acceleration and/or gyroscope as a MA reference. We propose an adaptive MA reference selection approach using acceleration and gyroscope signals. Our proposed approach can be used in other MA cancelation methods for the HR estimation error reduction. We believe this study will help many researchers studying wearable devices to understand accelerometer and gyroscope sensors. Abstract: Background and objective: Recently, various algorithms have been introduced using wrist-worn photoplethysmography (PPG) to provide high accuracy of instantaneous heart rate (HR) estimation, including during high-intensity exercise. Most studies focus on using acceleration and/or gyroscope signals for the motion artifact (MA) reference, which attenuates or cancels out noise from the MA-corrupted PPG signals. We aim to open and pave the path to find an appropriate MA reference selection for MA cancelation in PPG. Methods: We investigated how the acceleration and gyroscope reference signals correlate with the MAs of the distorted PPG signals and derived both mathematically and experimentally an adaptive MA reference selection approach. We applied our algorithm to five state-of-the-art (SOTA) methods for the performance evaluation. In addition, we compared the four MA reference selection approaches, i.e. with acceleration signal only, with gyroscope signal only, with both signals, and using our proposed adaptive selection. Results: When applied to 47 PPG recordings acquired during intensive physical exercise from two different datasets, our proposed adaptive MA reference selection method provided higher accuracy than the other MA selection approaches for all five SOTA methods. Conclusion: Our proposed adaptive MA reference selection approach can be used in other MA cancelation methods and reduces the HR estimation error. Significance: We believe that this study helps researchers to address acceleration and gyroscope signals as accurate MA references, which eventually improves the overall performance for estimating HRs through the various algorithms developed by research groups.